2017
DOI: 10.1021/acsami.7b13727
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Liver Matrix-Modified Cryogel Scaffolds as Potential Hepatocyte Carriers in Bioartificial Liver Support Systems and Implantable Liver Constructs

Abstract: Recent progress in the use of decellularized organ scaffolds as regenerative matrices for tissue engineering holds great promise in addressing the issue of donor organ shortage. Decellularization preserves the mechanical integrity, composition, and microvasculature critical for zonation of hepatocytes in the liver. Earlier studies have reported the possibility of repopulating decellularized matrices with hepatic cell lines or stem cells to improve liver regeneration. In this work, we study the versatility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…Despite the DLM‐based biomaterial providing the hepatocytes with a better 3D architecture, the hepatocytes are unable to maintain a steady growth rate for extended periods of time, and even lose their viability and functions after 5 days of culture. Similar results were also found in a previous study (Damania et al, ). Hepatocytes spheroid, which can create an efficient 3D tissue construct for maintaining hepatic functions for a long‐term culture may be carried out as a suitable cell source for further optimization of this promising research.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Despite the DLM‐based biomaterial providing the hepatocytes with a better 3D architecture, the hepatocytes are unable to maintain a steady growth rate for extended periods of time, and even lose their viability and functions after 5 days of culture. Similar results were also found in a previous study (Damania et al, ). Hepatocytes spheroid, which can create an efficient 3D tissue construct for maintaining hepatic functions for a long‐term culture may be carried out as a suitable cell source for further optimization of this promising research.…”
Section: Discussionsupporting
confidence: 93%
“…Glt‐HPA‐DLM as a 3D culture environment can effectively enhance the viability and functions of hepatocytes (Figure ). Previous study has been reported that decellularized liver ECM‐based scaffold can alleviate the injury conditions after partial hepatectomy treatment to some extent; besides, AST and ALT were decreased whereas bilirubin and albumin were increased after transplantation in vivo (Damania et al, ). In this study, the efficiency of DLM‐based biomaterial for ameliorating hepatotoxicants‐induced damaged hepatocytes is summarized below:…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, hepatic carcinoma cells are competent alternative which are easy and inexpensive to culture. Further, in our previous study, we found no significant differences between primary hepatocytes and HepG2 cell lines in terms of relevant cell functionalities, when grown on a cryogel 3D matrix and implanted in vivo (Damania et al, 2018). Therefore, to demonstrate proof of concept, we used HepG2 cells to establish an ectopic liver using injectable approach due to the limited supply of freshly isolated primary human hepatocytes and minimizing animal use.…”
Section: Discussionmentioning
confidence: 97%
“…By using the ECM of an acellularized liver, which can be integrated into the scaffold matrix, the highest similarity with the in vivo conditions can be achieved [50]. During decellularization, cells and other immunogenic factors are removed and only the natural scaffold of tissue remains.…”
Section: Decellularization/recellularization Approachmentioning
confidence: 99%